Questions of communication between hearing impaired and deaf patients in medicine - A. A. Sidorov; N. N. Bondarenko (Кубанский научный медицинский вестник, 2014)
A review of literature on the general concept of “communication” between people was held. History of the communication development and modern achievements of communication people. The methods of interpersonal communication between people, and especially physician-patient relationship are taken up. Usage of the verbal and nonverbal means of communication by the hearing impaired. Analyzed the essence of the communicative process. Examined the methods of communication between the dentist and the hearing-impaired patient, and the main problems that are appearing during the communication between the dentist and the hearing-impaired patient. The role of a sign language interpreter in the doctor-patient relationship. Conducted a review of the auxiliary means of communication, their advantages and disadvantages. The use of computer technology and software to translate oral speech into sign language. Identified the main problems of hearing-impaired and deaf patients, associated with their medical care.